PENCARIAN LOKASI FOTOGRAFI ASIA HERTITAGE BERBASIS LOCATION BASED SERVICE (LBS) MENGGUNAKAN ALGORITMA A-STAR - Pandapotan, Boris Yosua; Nasien, Dewi (Jurnal Manajamen Informatika Jayakarta, 2024)
This research is conducted by Asia Heritage Pekanbaru, which is one of recreational culinary and tourism in Pekanbaru. Asia Heritage offers comprehensive options of attractions, culinary, and photography spots. Still, it has considerable setbacks being less en-route information and signs and pictures to symbolize the tracks en route to the place. This research is on developing a Location Based Service (LBS) application that utilizes A Star Algorithm. This application can detect object position and generates the shortest effective routes to the designated spot by using A Star Algorithm's active reaction to the entitled class. This research later reveals an application named "Asia Heritage." It is a Photographic application that helps and gives the user the features of available photo-on spots, location, attractions, detailed information, and creative editing for a unique and magnifying experience for each user.